Travel in the Age of Social Media: From Likes to Destinations - Alamova Rano (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This paper analyses how social media platforms have impacted the global tourism sector, transforming current traveler behavior. In analyzing how platforms such as Instagram, TikTok and Youtube have impacted the selection of tourist destinations, the planning of holidays, as well as a traveler's perception of tourism, the paper will incorporate both literature and qualitative analysis of the internet phenomenon. It will discuss how traveler demand can be impacted by user-generated content and influencer marketing. The article will illustrate how the platforms allow for greater accessibility of information, access to destinations as well as offering travel ideas and inspiration, however, the platforms contribute to issues such as over-tourism, a detrimental impact on the environment and the commercialization of what once used to be authentic travel. The conclusion drawn is that even though social media is contributing to a more interconnected global community, it is fundamentally changing reasons for travel from the discovery and experience of a new culture, to more of a passive and consumption based activity of photo opportunities and social validation.